Comparative metabolic study of the chloroform fraction of three Cystoseira species based on UPLC/ESI/MS analysis and biological activities - Shaza H. Aly; Ahmed M. Elissawy; Mahmoud A. El Hassab; Taghreed A. Majrashi; Fatma E. Hassan; Eslam B. Elkaeed; Wagdy M. Eldehna; Abdel Nasser B. Singab (Journal of Enzyme Inhibition and Medicinal Chemistry)
This study aims to investigate the phytoconstituents of the chloroform fraction of three Cystoseira spp. namely C. myrica, C. trinodis, and C. tamariscifolia using UPLC/ESI/MS technique. The results revealed the identification of 19, 20 and 11 metabolites in C. myrica, C. trinodis, and C. tamariscifolia, respectively mainly terpenoids, flavonoids, phenolic acids and fatty acids. Also, an in vitro antioxidant study using FRAP and DPPH assays was conducted where the chloroform fraction of C. trinodis displayed the highest antioxidant activity in both assays, which would be attributed to its highest total phenolics and total flavonoids. Besides, the investigation of COX-1, α-glucosidase and α-amylase inhibitory activities were performed. Regarding C. trinodis, it showed the strongest inhibitory activity towards COX-1. Moreover, it showed potent inhibitory activity towards α-glucosidase and α-amylase enzymes. According to the molecular docking studies, the major compounds characterised showed efficient binding to the active sites of the target enzymes.